Effect of Training and Development Programs on Employee Productivity in Mozambique - Eli, Elias (European Journal of Human Resource, 2024)
Purpose: The aim of the study was to assess the effect of training and development programs on employee productivity in Mozambique. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that well-structured training initiatives lead to significant improvements in both individual and organizational performance. Employees who undergo regular training acquire new skills and knowledge, which can be directly applied to their job tasks, leading to increased efficiency and effectiveness. Furthermore, development programs foster a sense of growth and career advancement, boosting employee morale and motivation. This, in turn, reduces turnover rates and enhances job satisfaction. Organizations that invest in continuous learning opportunities often see a more engaged and competent workforce, capable of adapting to changing business environments and driving innovation. Ultimately, the strategic implementation of training and development programs can lead to a more productive and competitive organization, with employees who are well-equipped to meet current and future challenges. Implications to Theory, Practice and Policy: Human capital theory, social learning theory and motivation-hygiene theory may be used to anchor future studies on assessing the effect of training and development programs on employee productivity in Mozambique. Organizations should design and implement customized training programs that align with specific job roles and organizational objectives. Policymakers should promote policies that support lifelong learning and professional development. This includes providing incentives for organizations to invest in employee training and development programs.